The status of hospital dentistry in Taiwan in October 2019 - Feng-Chou Cheng; Julia Yu-Fong Chang; Tzu-Chiang Lin; Po-Fang Tsai; Yung-Ta Chang; Chun-Pin Chiang (Elsevier, 2020)
Background/purpose: Dental care has been officially incorporated into the hospital accreditation system in Taiwan since 2015. The geographical distribution of dentist manpower still remains in an unbalanced status as shown by the dentist-to-population ratio. This study tried to assess the dental manpower issue in terms of the status of hospital dentistry, and hence provided two organizational-level suggestions with their policy implications. Materials and methods: This study utilized the secondary data analysis to evaluate the dental manpower in dental departments of medical centers, regional hospitals, and district hospitals in different regions of Taiwan in October 2019. Results: Our results found that the dental manpower including the numbers of general dentists and dental specialists was highest in medical centers, followed by regional hospitals and district hospitals. Moreover, the dental resources and manpower were mostly concentrated in the northern region of Taiwan, followed by the central and southern regions of Taiwan, the eastern region of Taiwan, and offshore islands. Conclusion: The hospital dentistry in Taiwan develops toward large-scale and specialization. Both hospital general dentists and dental specialists are concentrated in the medical centers, especially the medical centers in the northern region of Taiwan, indicating the problem of oversupply in the northern Taiwan and unbalanced distribution of dentists among the regions in Taiwan. Therefore, the responsibilities of the hospitals in metropolitan areas are to develop the elderly and disabled dentistry and to assist with oral health promotion and oral disease prevention in remote areas to reduce the urban-rural gap in dental resources in Taiwan.